Cryoablation for persistent and longstanding persistent atrial fibrillation: results from a multicentre European registry. Issue 3 (6th December 2019) - Sawhney, Vinit; Schilling, Richard J; Providencia, Rui; Cadd, Matthew; Perera, Dhanuka; Chatha, Salman; Mercer, Ben; Finlay, Malcolm; Halimi, Franck; Pavin, Dominique; Anselme, Frederic; Cebron, Jean-Pierre; et al.
Abstract: Aims: Although cryoballoon pulmonary vein isolation is a well-established treatment for paroxysmal atrial fibrillation (AF), it's role in persistent AF is unclear. We examined procedural success and long-term outcomes of cryoablation in persistent and longstanding persistent AF. Methods and results: International multicentre registry from three UK and eight European centres. Consecutive patients undergoing cryoablation for persistent AF included. Procedural data, complications, and follow-up were prospectively recorded. Patients were followed-up at 3, 6, and 12 months with an electrocardiogram with open access to arrhythmia nurses thereafter. Ambulatory monitoring was dictated by symptoms. Success was defined as freedom from AF or atrial tachycardia lasting >30 s off antiarrhythmic drugs (AADs). Six hundred and nine consecutive cryoablation procedures. Mean procedure and fluoroscopy times were 95 ± 65 and 13 ± 10 min. Single procedure success rates were 368/602 (61%) off AADs over a median of 2.4 (1.0–4.0) years. Arrhythmia-free survival off AADs was 64% and 57% for persistent and longstanding persistent AF at 24 months of follow-up ( P = 0.02). Rate of repeat ablations was 20% in persistent and 32% in longstanding persistent AF ( P = 0.006). Cox regression analyses showed a significant association between duration of AF and left atrial diameter and arrhythmia recurrence [hazard ratio (HR) 1.05, P -value 0.01 and HR 1.02, P -value 0.004]. Conclusion: Cryoablation for persistent AF is safe, fast and has good outcomes at long-term follow-up. Cryoablation is reasonable as a first line option for these patients. Short procedure times may help increase capacity of cardiac units to meet the rising demand for AF ablation. Randomised control trials are needed to compare outcomes with different techniques.